Simulation and hardware-in-the-loop evaluation of dual boost converter with shared transformer - part A - Seetoh, Winston Zit Yang (2018)
This report presents the study of Advanced Control Systems for Dual Boost Converter with Shared Transformer. The single-inductor-single-input-dual-output (SISIDO) buck converters (DC-DC) in this report adopts a single inductor/transformer i.e. the output loads share a single inductor/transformer. Using only one inductor/transformer leads to reduction of component number, cost and circuit size when compared with conventional multi-load system which uses many single-input-single-output (SISO) converters. In addition, the use of single inductor/transformer reduces electromagnetic interference (EMI) problem. In multi-load system with many SISO converters, EMI problem can be serious if the number of inductors/transformers are significant.